2017
DOI: 10.3389/fphys.2017.00434
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inflammation and Downstream Protein Metabolism in Sarcopenia: A Brief Up-Dated Description of Concurrent Exercise and Leucine-Based Multimodal Intervention

Abstract: Sarcopenia is defined as the progressive loss of muscle mass with age, and poses a serious threat to the physiological and psychological health of the elderly population with consequential economic and social burdens. Chronic low-grade inflammation plays a central role in the development of sarcopenia such that it alters cellular protein metabolism to favor proteolysis over synthesis, and thereby accelerates muscular atrophy. The purpose of this review is to highlight how exercise and nutrition intervention st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 48 publications
0
38
0
2
Order By: Relevance
“…49) This finding can be largely explained by the mechanism of muscle protein breakdown, i.e., the progression of sarcopenia. 47) We hypothesize that pre-existing sarcopenia caused partly by systemic inflammation might have meaningful effects on rehabilitation outcomes, even though a causal relationship between systemic inflammation and sarcopenia was not clear in the current study because of its design. We believe that it is important to be aware of the influence of systemic inflammation on functional outcomes in the relevant study fields.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…49) This finding can be largely explained by the mechanism of muscle protein breakdown, i.e., the progression of sarcopenia. 47) We hypothesize that pre-existing sarcopenia caused partly by systemic inflammation might have meaningful effects on rehabilitation outcomes, even though a causal relationship between systemic inflammation and sarcopenia was not clear in the current study because of its design. We believe that it is important to be aware of the influence of systemic inflammation on functional outcomes in the relevant study fields.…”
Section: Discussionmentioning
confidence: 78%
“…It has also been shown that depletion of muscle mass with aging is caused by inflammatory cytokines produced by chronic low-grade inflammation. 47) Inflammatory cytokines suppress protein synthesis pathways including that of the mammalian target of rapamycin. Inflammatory cytokines also activate the ubiquitin / proteasome pathway (UPP) which promotes the breakdown of muscle proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the population continues to age within Europe, an increase in the incidence of age-related diseases is observed (WHO 2017). Indeed, the increasing lifespan is not associated with an increase in health span, and this issue represents a great challenge for our societies.…”
Section: Introductionmentioning
confidence: 99%
“…A possible strategy to impact on aging is to intervene on lifestyle factors, such as diet or physical activity. Nutritional interventions seem to be one of the most promising approaches to promote healthy aging, and growing amount of data indicates that they can influence the health status of subjects (Longo et al 2015;Dato et al 2016;Wahl et al 2016;Shlisky et al 2017;Xia et al 2017;Heiss et al 2017).…”
Section: Introductionmentioning
confidence: 99%